Eksistensi BPK dalam Melakukan Pengawasan Keuangan Negara - Moh. Annand Ananda Saputra; Aryo Dwiarief Susetyo; Rachmat Hidayat (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the strategic role of the Supreme Audit Agency (BPK) of the Republic of Indonesia in ensuring transparent, accountable, and aligned state financial management in line with national goals. As an independent state institution, the BPK has a constitutional mandate to audit state financial management and accountability objectively and free from intervention by any party. This study uses a legal method with a normative juridical approach, accompanied by descriptive analysis and systematic interpretation of data from literature studies. The results show that the BPK has broad authority in auditing state finances, both for the central government, regional governments, and other public institutions. However, its implementation still faces obstacles such as a lack of internal transparency, overlap with internal government oversight, and limited resources for comprehensive oversight. To address these issues, the BPK needs to strengthen its internal systems, increase auditor capacity, develop more systematic audit result reporting guidelines, and build cross-agency coordination to make its external oversight function more effective, transparent, and capable of supporting clean and integrated governance.